Electrochemical Impedance Spectroscopy of Polyvinylalcohol Based Gel Electrolyte - Nirwan Syarif; Nurlisa Hidayanti; Edy Herianto Majlan; Monica Sari Jayanti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Research on the effect of electrolyte ammonium salt, concentration electrolyte with plasticizer to ionic and electronic conductivity of polymer gel electrolyte has been conducted with the variations of two electrolyte NH4Cl-PVA and NH4SCN-PVA at a concentration of 10, 30, 40 (wt%). The measurement of using ionic conductivity by using impedance spectroscopy method showed that the highest value was 0.0156 Scm-1 i.e. in the 54.6% propilen carbonate with 40% NH4Cl and PVA. The lowest value was 0.009 Scm-1 i.e. in the NH4SCN based electrolyte without propilene carbonate and electronic conductivity showed that the highest value was 0.0156 Scm-1 i.e. 40% NH4Cl-PVA and NH4SCN-PVA and the lowest value was 0.009 Scm-1, i.e. in the NH4SCN based electrolyte without propilene carbonate. Factorial analyses showed that the concentrations of electrolyte and the plasticizer affect conductivity value. FTIR (Fourier Transform Infrared) measurement showed that the addition of propilene carbonate did not show new bond formation between electrolyte and PVA. It can be shown in absence of characteristic wave number for propilene carbonate and NH4+ ion.Keywords: DOE, plasticizer, propylenecarbonate, ionic, electronic, conductivity